PELATIHAN PENGEMBANGAN KARAKTER SISWA SMK 1 MA'ARIF SLEMAN YOGYAKARTA BERBASIS NILAI KEBUDAYAAN PESANTREN - Rachmadani, Fadhila; Rohman, Arif; Anwar, Muhammad Saiful; Widijantoro, Noor (Al-Umron : Jurnal Pengabdian Kepada Masyarakat, 2025)
This research, which was conducted in one unit with community service activities, aims to provide character development training for students based on Islamic boarding school values ​​at SMK 1 Ma'arif, Sleman, Yogyakarta. This research is based on a sense of concern about the increasing number of juvenile delinquencies among high school students. Juvenile delinquency is triggered by several factors such as globalization, modernization, and the rapid development of information technology. This research focuses on efforts to minimize the negative impacts of these factors. This research uses a focus group discussion or FGD data collection method involving 18 respondents. This qualitative research uses the theoretical framework of Imam Al-Ghazali's philosophical thought, in order to analyze reflectively-philosophically the values ​​of Islamic boarding school culture as a basis for developing character education for students at SMK 1 Ma'arif, Sleman, Yogyakarta. The community service activities used were the lecture method and action plan assistance. The lecture method is used to convey material related to the values ​​of Islamic boarding school education in order to build the character of adolescents at SMK 1 Ma'arif, Sleman, Yogyakarta. This action plan mentoring method, participants are asked to submit a proposal for "Development of Student Activities at SMK 1 Ma'arif, Sleman, Yogyakarta through the Habituation of Pesantren Culture". The implementation of this research and community service activity was carried out at SMK 1 Ma'arif, Sleman, Yogyakarta. The target of this research and community service activity is the participants of the Student Character Development Training Based on Pesantren Values ​​at SMK 1 Ma'arif, Sleman Yogyakarta. The results of this research and community service activity, training participants get benefits that contribute to self-development in terms of insight, intellectual, personal, and professional.